A study on 100% Nylon used for local-manufactured leotards - Nepomuceno, Tasha Monina H.
The leotard is a very essential garment for the dancer. It is the dancer's basic uniform which should provide for high-quality garment performance. This study was conducted in order to determine the quality of the fabric used for the manufacture of local ready-made leotards. It also wants to know if said fabrics fulfill the needs and expectations of ballet dancers in relation to the nature of their activity. Three major objectives were met in the study. The fiber content of the fabric used for locally manufactured leotards specifically that of the brand, Yvonne's was identified. With the assistance of the Philippine Textiles Research Institute, the fabric was tested and fiber content was identified as 100% Nylon. Second, to evaluate the suitability of fabrics used for locally-manufactured leotards to its end-use, the leotards (Yvonne's) were tested for Dimensional Change due to Laundering and Colorfastness to Laundering. The last objective was to determine the satisfaction of the ballet dancers as users of the leotards. The comments of the dancers about locally-manufactured leotards were determined and used as the basis for explaining the fabric's performance as against expectations and concerns of the dancers. Survey results show that majority of the respondents are dissatisfied with the quality of leotards, particularly with the fabrics used for their production. There were specific issues which were identified in the survey and a fabric sample was tested to support the dancers' observations. The fabric sample was tested for Colorfastness to Laundering and Dimensional Change due to Laundering. The data from the laboratory tests showed that technical requirements for the quality of the fabric have been met according to the standards set by the American Standards for Testing and Materials. In conclusion, the laboratory tests which were conducted identified the fabric standards of the manufacturer which were acceptable. However, long-term performance of the fabric showed how the changes in the leotards' shape and dimensional stability are affected and as such validated the concerns and issues of the ballet dancers as respondents.